Monitoring the time-averaged discharge rates, volumes and emplacement style of large lava flows by using MIROVA system: the case of the 2014-2015 eruption at Holuhraun (Iceland) - Coppola, Diego; Barsotti, Sara; Cigolini, Corrado; Laiolo, Marco; Pfeffer, Melissa Anne; Ripepe, Maurizio (Annals of Geophysics, 2019)
The 2014-2015 eruption at Holuhraun has produced more than 1.5 km3 of basaltic magma and can beconsidered one of the major effusive events of the last two centuries in the world. During this eruptionthe MIROVA system (a volcanic hot-spot detection system based on MODIS middle infrared – MIR- data) has been used to detect and locate the active portions of the lava flow(s), and to measure the heat radiated by the growing lava field. According to these data the eruption was characterized by a slow decay of the radiant power, accompanied by a change in the lava transport mechanism that shifted from open channels, at the beginning of the eruption, to lava tubes, during the last months of activity. Despite the evident evolution of lava transport mechanism, we found that the overalldecreasing trend of the thermal flux was mainly controlled by the exponential decline of lava discharge rates, while the increasing insulation of the flow field had a strong impact in transporting efficiently the lava at the distal flow front(s). Our results suggest the apparent time averaged lava discharge rates (TADR), derived from satellite thermal data, may fluctuate around the real effusion rate at the vent, especially in the case of large lava flows emplacing in nearly flat conditions. The magnitude and frequency of these fluctuations are mainly controlled by the emplacement dynamic,(i.e. occurrence of distinct major flow units), while the transition from channel- to tube-fed lavatransport mechanism play only a minor role (±30%) in the retrieval of TADR using MIR data . Whenthe TADR values are integrated to calculate erupted lava volumes, the effects of pulsatingemplacement dynamic become smoothed and the eruptive trend become more clear.We suggest that during the Holuhraun’s eruption, as well as during many other effusive eruptions,the MIR-derived radiant flux essentially mimic the overall trend of lava discharge rates, with only aminor influence due to the emplacement style and evolving eruptive conditions. From a monitoringand ...